Completion Dynamics Conflict Political Constitution in Indonesia Through Values Approach Religiousness Jurisprudence Maqashidus Syariah - Irwansyah Irwansyah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Negative ambition, thirst for power, which gives birth to fraud in constitutional politics, greed will tend to give birth to authoritarian government, which also facilitates uncontrolled corrupt behavior in all levels of the government system, the result is that corruption becomes a system that is difficult to judge effectively. right in front of the judiciary. The state's ideals which are the legal basis in the Proclamation are only historical, the State's goals as stated in Paragraph IV appear to be subject to multiple interpretations with negative ambitions and a monopoly in the control of natural resources by certain groups. The Constitutional Court has become a bone of contention. because it is considered the last bull of the constitution. The various systems and regulations as the basic foundation in the 1945 Constitution are the reason that it is no longer appropriate to the situation and must be repeatedly amended. The recruitment of State Rulers through the ELECTION system once every five years continues to be changed in a direction that is increasingly widening and even eliminating the true meaning of the goals of a State which is based on the Blessing of God. Almighty. Our constitutional history, which is quite long since the birth of the 1945 Constitution, will continue to be corrected for reasons of adjusting interests. In fact, the state is a tool to achieve the goals of the nation that agreed to form the state with the aim of protecting and ensuring the welfare of the people of that nation. The principles and foundations of the State have been established as the foundation in a state order, but our constitutional problems can only be resolved by changing the law and very minimally changing the concept of human thinking in that Pancasila has become the philosophy and goal of national life. The next question will be whether the Amendment to the 1945 Constitution will continue. carried out to adjust the circumstances of the desires or interests of the State authorities. Conflicts of interest in our state structure must return to the order of religious values ​​in religion which in Islamic psychology is known as Maqashidus syari'ah jurisprudence.